2014
DOI: 10.1371/journal.ppat.1004520
|View full text |Cite
|
Sign up to set email alerts
|

The Central Role of cAMP in Regulating Plasmodium falciparum Merozoite Invasion of Human Erythrocytes

Abstract: All pathogenesis and death associated with Plasmodium falciparum malaria is due to parasite-infected erythrocytes. Invasion of erythrocytes by P. falciparum merozoites requires specific interactions between host receptors and parasite ligands that are localized in apical organelles called micronemes. Here, we identify cAMP as a key regulator that triggers the timely secretion of microneme proteins enabling receptor-engagement and invasion. We demonstrate that exposure of merozoites to a low K+ environment, typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
138
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(144 citation statements)
references
References 50 publications
6
138
0
Order By: Relevance
“…6), which are known to play important roles in pathogenesis [6, 30]. P. falciparum , the species responsible for the majority of malariarelated deaths, has three CNB-containing proteins, namely PfPKA-R, PfPKG and Rap guanine nucleotide exchange factor (PfEpac) [15]. P. vivax, P. berghei, P. yoelii, P. knowlesi, P. reichenowi, and P. chabaudi also encode multiple CNB domains in their genomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6), which are known to play important roles in pathogenesis [6, 30]. P. falciparum , the species responsible for the majority of malariarelated deaths, has three CNB-containing proteins, namely PfPKA-R, PfPKG and Rap guanine nucleotide exchange factor (PfEpac) [15]. P. vivax, P. berghei, P. yoelii, P. knowlesi, P. reichenowi, and P. chabaudi also encode multiple CNB domains in their genomes.…”
Section: Resultsmentioning
confidence: 99%
“…Even if the role of S610 phosphorylation in invasion has not been clearly demonstrated, PKA-mediated phosphorylation of a wide range of parasite proteins takes place prior to merozoite egress [14]. Merozoite egress and reinvasion of new red blood cells depend on cAMP-dependent PKA [15] and merozoite egress can also be regulated by cGMP-PKG [9,16]. Clearly, both cAMP and cGMP are critical secondary messengers in malaria parasite biology.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cAMP has been identified as a key regulator that triggers the timely secretion of microneme proteins, enabling receptor engagement and invasion [22]. This study also observed that cAMP increases merozoite cytosolic Ca2+ levels via induction of the Epac pathway; together, they are involved in the invasion process [22].…”
Section: Introductionmentioning
confidence: 73%
“…This study also observed that cAMP increases merozoite cytosolic Ca2+ levels via induction of the Epac pathway; together, they are involved in the invasion process [22]. Moreover, our group reported that the cAMP analog adenosine 3′,5′-cyclic monophosphate N6-benzoyl/PKA activator (6-Bz-cAMP) is able to increase the schizont (S) stage, leading to progression of the asexual stage of the life cycle and modulation of PFNF-YB transcription factor expression during the intraerythrocytic cycle in P. falciparum [23].…”
Section: Introductionmentioning
confidence: 89%
“…http://dx.doi.org/10.1101/265371 doi: bioRxiv preprint first posted online Feb. 14, 2018; the cytoplasmic tail of the parasite adhesin AMA1 22,23 and may be linked to Ca 2+ signalling 13 .…”
mentioning
confidence: 99%